Analysis of Nutrition Knowledge, Food Pattern, Nutritional Status And Physical Fitness of Football Soccer Sports In Duduksampeyan Sub-District, Gresik District - Mufidatul Maziyah (Ghidza Media Jurnal, 2021)
This study is aimed to analyze the provision of nutrition education on nutrition knowledge, food pattern, nutritional status and physical fitness to soccer players in the Duduksampeyan Sub-District, Gresik District. This research is pre-experiment with the one group pretest-posttest design approach. Sampling with a total sampling technique of 68 male respondents who met the inclusion criteria. Education is carried out in one meeting. Data collection with questionnaires and measurements before and after education. Analysis of the differences before and after treatment was carried out using the Wilcoxon test and paired t-test. There were differences in the mean knowledge of nutrition before and after education is given, but there were no differences in food pattern, nutritional status, and physical fitness before and after education is given.